The Impact of Catholic School Identity and Organizational Leadership on the Vitality of Catholic Elementary Schools - Hobbie, Marian; Convey, John J.; Schuttloffel, Merylann J. (Catholic Education: A Journal of Inquiry and Practice, 2010)
In order to fulfill their role of teaching children to receive Jesus and live out his call to create the Kingdom of God on earth and in heaven, Catholic schools need to possess and foster the distinctive characteristics of Catholic school identity. This study examined the relationship between Catholic school identity and organizational leadership and the extent to which these predict aspects of school vitality in Catholic elementary schools. The results of the analyses point to the signifi cant predictive relationship of Catholic school identity on each subscale of school vitality and at least one subscale of organizational leadership on three of the four subscales of school vitality. In addition, years of teaching in Catholic schools and percent of Catholic students are signifi cant predictors of Catholic school identity.